Untamed - Cam 1984- (Nashville, Tennessee? New York, NY Sony Music Entertainment Arista Nashville, 2015)
Chosen as one of CMT's Next Women of Country, Cam is following up her successful Welcome to Cam Country EP with her debut full-length album. Her first single, Burning House, is quickly rising up the country charts.
Untamed -- Hungover on heartache -- Mayday -- Burning house -- Cold in California -- My mistake -- Runaway train -- Half broke heart -- Want it all -- Country ain't never been pretty -- Village.
All songs co-written by Cam.
Title from disc label.
Credits inserted in container.
Produced by Jeff Bhasker and Tyler Johnson.
Performed by Cam; with accompanying musicians.
104523
Keywords: 2011 - 2020; Country music -- 2011-2020.; Country; Songs; Country music; Country music; Songs; Country